THE EFFECT OF MOTIVATION AND INCENTIVE GIVING ON EMPLOYEE PERFORMANCE OF PT. ACOSTA IN MEDAN - Sariyanto, Sariyanto; Rahmayati, T. Elfira; Adriansyah, T. Muhammad; Azulaidin, Azulaidin (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study aims to determine the effect of motivation on employee performance, determine the effect of incentives on employee performance, and determine the effect of motivation and incentives together on employee performance. The research methodology used is quantitative, real research figures and how discussions with statistical tests. The population used in this study were employees working at PT. Acosta Group and the sample used in this study was 74 respondents with questionnaire data collection. Partial results on employee performance in done by motivation (X1) proven to have a positive and significant effect on performance (Y) with a large influence of t count (4.195) greater than the t table value (1.667) and sig, t for the motivation variable (0.000) smaller with alpha (0.05), the effect of partial motivation to improve employee performance at PT. Acosta Group. The value is the perception carried out by the incentive variable (X2) is stated positively and has an influence on performance (Y) by the influence of t count (2.944) greater than the t table value (1.667) and sig, t for the incentive variable (0.004) smaller with alpha (0.05), the effect of partial incentives on improving employee performance at PT. Acosta. Motivation and Incentive variables simultaneously have a significant influence on employee performance of F count (18,086) which is greater than the F table value (3.13) with a determination coefficient of 0.338, meaning that 33.8% of the performance variable can be explained by motivation and incentive variables, while the remaining 66.2% can be explained by other variables, with the same value as the study variables.